CC* cyber team: creating a community of regional data and workflow cyberinfrastructure facilitators - Hauser, Thomas, author; Burns, Patrick J., author; Cheatham, Thomas E., author; Siegel, H. J., author; Williams, James, author (Colorado State University. Libraries, 2017)
The Rocky Mountain Advanced Computing Consortium (RMACC), represented by the University of Colorado Boulder, the University of Utah and Colorado State University, propose to create a distributed cyberinfrastructure (CI) team of data and workflow facilitators ("Cyberteam" or "CI Facilitators") for experimental and observational science (EOS). Advances in the number and diversity of data sets require enhanced capabilities to access, reuse, process, analyze, understand, curate, share, and preserve data. A critical aspect in dealing with such large, diverse data sets is to provide expert support for efficient and effective workflows involving data generation, data analysis, visualization, and preservation. Typically, data management, analysis, sharing and curation have been the responsibilities of individual researchers. As a result, data can be difficult to reuse by anyone other than the originators. Likewise, computational and data generation workflows are often cobbled together, hard-coded, and not readily amenable for sharing. These problems must be addressed to make workflows and data available for reuse, and to reuse others' data. The proposed work will fund three FTEs to provide such support for science projects on the three partner campuses as well as projects in the region under the auspices of the RMACC. We note that while each of these institutions having strong support for research computing and the libraries, none at present have facilitators of this type.
The University of Colorado, Colorado State University, and the University of Utah propose the formation of a distributed, three-person experienced Cyberteam to provide needed cyberinfrastructure (CI) support to researchers at institutions in the Rocky Mountain Advanced Computing Consortium (RMACC) encompassing the states of Colorado, Idaho, New Mexico, Utah, and Wyoming. Based on experience supporting experienced and new researchers needing CI, it is obvious that there is a new, profound need for "cradle to grave" support for all for the complexity inherent in the reuse of data for reproducibility and extension to new discovery. Researchers need assistance in both publishing their data for further research, and finding, accessing, and using others' published data. Next generation workflows must be supported, while maintaining intellectual property, security, and privacy. This proposal is to add one Cyberteam expert at each of the three lead institutions to provide researcher support, training, and outreach for all RMACC institutions. UNIVERSITY OF COLORADO - User support for CI "cradle to grave" next generation workflows, encompassing data access, preprocessing (including "data carpentry" for reuse), storage, transport, computation, and postprocessing (including basic and advanced scientific visualization, interpretation, and preservation). COLORADO STATE UNIVERSITY - Support for data management and preservation, including making their shared digital repository and data management expertise available to all in the RMACC region. This is particularly germane for smaller institutions, which have no mechanism for this. UNIVERSITY OF UTAH - Maintenance of appropriate security, privacy, and access controls in the entire workflow process. Exploration of usable workflows through "templates" or similar virtualization technologies.
Keywords: cyberinfrastructure